Task content and job losses in the Great Lockdown - Filippos Petroulakis (Global Labor Organization (GLO), 2020)
I examine the short-term labor market effects of the Great Lockdown in the United States. I analyze job losses by task content (Acemoglu & Autor 2011), and show that they follow underlying trends; jobs with a high non-routine content are especially well-protected, even if they are not teleworkable. The importance of the task content, particularly for non-routine cognitive analytical tasks, is strong even after controlling for age, gender, race, education, sector and location (and hence for differential demand and supply shocks). Jobs subject to higher structural turnover rates are much more likely to be terminated, suggesting that easier-to-replace employees were at a particular disadvantage, even within sectors; at the same time, there is evidence of labor hoarding for more valuable matches. Individuals in low-skilled jobs fared comparatively better in industries with a high share of highskilled workers.
Keywords: D22; E32; J23; J24; M51; 330; COVID-19; Labor Markets; Recessions; Task Framework; Business Cycles; Unemployment